Spatially distinct Raman scattering characteristics of individual ZnO nanorods under controlled polarization: intense end scattering from forbidden modes. Issue 24 (12th June 2017) - Hansen, Matthew; Truong, Johnson; Xie, Tian; Hahm, Jong-in
Abstract : Position- and polarization-specific Raman scattering responses from individual ZnO nanorods (NRs) are determined and the unique, NR end-specific scattering behaviors per given polarization state are identified. Abstract : In this study, we characterize incident/scattered polarization-specific and NR position-resolved Raman scattering behaviors of individual zinc oxide nanorods (ZnO NRs). We quantify Raman signals from the five key ZnO phonon modes of E2L, E2H–2L, A1T, E1T, and E2H, and reveal the NR position-dependent Raman scattering characteristics of the phonon modes per given light–matter interaction geometry. We then present Raman intensity maps and elucidate Raman behaviors consistent and incongruous with Raman selection rules. In particular, we identify an intriguing Raman scattering phenomenon from the forbidden modes, distinctively occurring at the two NR ends. Their unexpectedly strong and localized scattering signals at the NR termini are contrasted by the scattering behaviors from the rest of the NR positions agreeing with the selection predictions. By carrying out control measurements on isotropic ZnO microparticles (MPs), we ascertain that the unique NR position-specific Raman responses observed on ZnO NRs originate from their high shape anisotropy. Owing to the superior optical property coupled with reduced dimensionality and high geometric anisotropy, ZnO NRs have gained much attention recently for use in optoelectronic, photonic, and biosensor technologies. Raman scattering has been increasingly exploited as a noninvasive and sensitive analytical tool to investigate NR properties pertinent to these applications. Hence, our endeavors, explicitly providing the spatially distinct, polarized Raman scattering behaviors from individual ZnO NRs, will be central to the correct interpretation of Raman data of both the individual and ensemble NRs as well as to the accurate correlation of the measurement outcomes to their chemical/physical/optical properties. Our efforts may also promote novel applications for polarized Raman scattering whose optical outputs on the various positions along the ZnO NRs can be selectively modulated.